2006
DOI: 10.1177/070674370605101305
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Psychiatrists' Current Attitudes, Practices, and Knowledge regarding Fitness to Drive in Individuals with Mental Illness: A Cross-Canada Survey

Abstract: Objectives: To assess current attitudes, practices, and knowledge of Canadian psychiatrists regarding fitness to drive in individuals with mental illness and to explore variations according to provincial legislation. Method:We carried out a national cross-sectional survey, using a random sample of psychiatrists. We used a mail survey to collect data. Results:In total, 248 psychiatrists participated; the response rate was 54.2% on traced subjects. The majority (64.1%) reported that they strongly agreed or agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
(26 reference statements)
5
25
0
2
Order By: Relevance
“…In comparison with other surveys concerning driver fitness problems, the response rate at 52% was in the average range [12][13][14][15][16][17][18][19][20][21][22]. To be especially noticed is the fact that practicing physicians were also approached who, in their specialty, have little or no relation to driving fitness problems (e.g., pediatricians, gynecologists).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other surveys concerning driver fitness problems, the response rate at 52% was in the average range [12][13][14][15][16][17][18][19][20][21][22]. To be especially noticed is the fact that practicing physicians were also approached who, in their specialty, have little or no relation to driving fitness problems (e.g., pediatricians, gynecologists).…”
Section: Discussionmentioning
confidence: 99%
“…Roughly, the same proportion was found in a Canadian study: depending on the province, between 14.6% and 29.3% of the psychiatrists did not know the legal regulations [15]. Portions in this magnitude, though, are to be understood with caution: in several investigations, when specific questions were asked, the portion of correct answers was distinctly lower.…”
Section: Discussionmentioning
confidence: 61%
“…In comparison, this proportion is rather low: in the literature, one finds approval rates of 83% to 97% [7,15,17]. Only half of the responding physicians feel a need for traffic medicine continuing education.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the majority of the Irish GPs surveyed (328, 71%) are confident in their abilities to assess MFTD, despite the literature suggesting that GPs often display uncertainty regarding the task (Jang et al 2007;Lipski 2002; Marshall and Gilbert 1999;Ménard et al 2006;Molnar at al. 2005).…”
Section: Discussionmentioning
confidence: 65%
“…These decisions are usually based on available MFTD guidelines ( to be as sensitive and responsive as possible to the modest but growing evidence base for MFTD (Beran 2013). A common motif throughout the literature is that often GPs are not aware of the standards set out in their national guidelines and, as a result, frequently report a lack of confidence when assessing MFTD (Jang et al 2007;Lipski 2002;Marshall and Gilbert 1999;Ménard et al 2006;Molnar et al 2005). A study in 1996 of GPs referring patients to syncope clinics showed them to be unclear about their responsibilities: only 13% of syncope patients were questioned on their driving by their doctor (MacMahon et al 1996).…”
Section: Introductionmentioning
confidence: 99%